Asymmetric syn‐1, 3‐Dioxane Construction via Kinetic Resolution of Secondary Alcohols Using Chiral Phosphoric Acid Catalysts. Issue 6 (6th May 2019) - Matsumoto, Akira; Asano, Keisuke; Matsubara, Seijiro
Abstract: Herein, we present a novel enantioselective hemiacetalization/intramolecular oxy‐Michael addition cascade for the synthesis of syn ‐1, 3‐diol frameworks via kinetic resolution of chiral secondary alcohols using chiral phosphoric acid catalysts. By utilizing the recovered optically active starting material, both enantiomers of the corresponding protected 1, 3‐diols could be obtained with high optical purities. In addition, the products with a carbonyl group were converted diastereoselectively to longer optically active 1, 3‐polyols, which are representative motifs in polyketides. Moreover, the organocatalytic approach presented in this study facilitates a library construction of useful chiral building blocks for the asymmetric synthesis of bioactive compounds. Abstract : Enantioselective hemiacetalization/intramolecular oxy‐Michael addition cascade for the synthesis of syn ‐1, 3‐diol frameworks via kinetic resolution of chiral secondary alcohols using chiral phosphoric acid catalysts has been reported. By utilizing the recovered optically active starting material, both enantiomers of the corresponding protected 1, 3‐diols could be obtained with high optical purities. In addition, the products with a carbonyl group were converted diastereoselectively to longer optically active 1, 3‐polyols, which are representative motifs in polyketides.